Relationship Strategy Coping with Self-Efficacy Drugs in the Period of Rehabilitation at Batam BNN Rehabilitation - Rachmawaty M Noer; Laily Fitriana; Mira Agusthia (Universitas Muhammadiyah Mataram, 2019)
In 2017, there were 26,540 drug users in Riau Islands. 3 out of 10 people who undergo rehabilitation has experienced relapse. If drug users can use coping strategies effectively, self-efficacy or confidence can develop well. The implication is that drug users can control themselves so as not to relapse. The purpose of this study was to examine the relationship between coping strategies and self-efficacy of drug users during rehabilitation. This research is correlational research. The instruments used in this study were the coping scale and self-efficacy. These instruments were used after being tested and declared as valid and reliable. The sample in this study were 35 people who were undergoing a program in the primary program and re-entry program at the Rehabilitation Workshop in BNN Batam which taken by cluster random sampling technique. The findings of this study are (1) the majority of the coping strategies of respondents are at a moderate level with a percentage of 88.57%; (2) the majority of respondents have high level self-efficacy with a percentage of 80%; and (3) there is a relationship between coping strategies and drug users' self-efficacy during the rehabilitation period with p value 0,011. It is expected that drug rehabilitation institutions can increase the level of coping strategies and self-efficacy of drug users in the rehabilitation period by teaching the coping skills and relapse prevention as well as exploring sources of self-efficacy.